2018
DOI: 10.1007/s00227-017-3279-6
|View full text |Cite
|
Sign up to set email alerts
|

Life-history responses to changing temperature and salinity of the Baltic Sea copepod Eurytemora affinis

Abstract: To understand the effects of predicted warming and changing salinity of marine ecosystems, it is important to have a good knowledge of species vulnerability and their capacity to adapt to environmental changes. In spring and autumn of 2014, we conducted common garden experiments to investigate how different populations of the copepod Eurytemora affinis from the Baltic Sea respond to varying temperatures and salinity conditions. Copepods were collected in the Stockholm archipelago, Bothnian Bay, and Gulf of Rig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 57 publications
(81 reference statements)
2
21
1
Order By: Relevance
“…We found a significant effect of salinity on development time at low salinity leading to a shorter development time for both the GOR and STHLM populations. This is in contrast with observations showing that freshwater conditions prolong development time for both freshwater and estuarine E. affinis populations (Karlsson et al, 2018; Lee et al, 2003). However, decreased salinity affects metabolic rates and ingestion rates of E. affinis , and freshwater tolerance increases if the copepods are exposed to sufficient food availability, as in our experiment (Hammock et al, 2016; Lee et al, 2013).…”
Section: Discussioncontrasting
confidence: 92%
See 2 more Smart Citations
“…We found a significant effect of salinity on development time at low salinity leading to a shorter development time for both the GOR and STHLM populations. This is in contrast with observations showing that freshwater conditions prolong development time for both freshwater and estuarine E. affinis populations (Karlsson et al, 2018; Lee et al, 2003). However, decreased salinity affects metabolic rates and ingestion rates of E. affinis , and freshwater tolerance increases if the copepods are exposed to sufficient food availability, as in our experiment (Hammock et al, 2016; Lee et al, 2013).…”
Section: Discussioncontrasting
confidence: 92%
“…Eurytemora affinis were collected with 90 µm vertical tow nets in autumn 2014 from the Bothnian Bay (BB, monitoring station F3A5, 65°10.14’, 23°14.41’), the Gulf of Riga–Pärnu Bay (GOR, 58°21.67’, 24°30.83’), and the Stockholm Archipelago–Askö (STHLM, monitoring station B1, 58°48.19’, 17°37.52’). The GOR population has in previous studies shown to develop to adult faster and at a larger size (Figure 1) than the STHLM population (Karlsson et al, 2018; Karlsson & Winder, 2018). Copepods were transported to the department in cooled conditions and placed in a cold room where temperature gradually increased up to 17°C over the course of several days.…”
Section: Methodsmentioning
confidence: 82%
See 1 more Smart Citation
“…Compared to the SBP where salinity is higher, the availability of copepod eggs in the low-saline NBP can be a larger source of energy for benthic macrofauna populations (Karlson & Viitasalo-Frösen, 2009). In addition, because the hatching rate is slower in low salinity (Karlsson et al, 2018) the accumulation of a seed bank followed by subsequent hatching could enhance the benthic-pelagic coupling. Our results highlight important geographic differences in meiofaunal communities that are only possible to uncover with modern molecular tools (Fonseca et al, 2010).…”
Section: Geographical Differences In Community Compositionmentioning
confidence: 99%
“…They play an important role in the transmission of energy between producers and consumers of higher orders, being food for many pelagic, planktivorous fish (Williams, Conway & Hunt, 1994; Froneman et al, 1996). Their abundance is highly dependent on the physicochemical variables of the environment (Möllmann, Kornilovs & Sidrevics, 2000; Möller et al, 2015; Karlsson, Puiac & Winder, 2018). …”
Section: Introductionmentioning
confidence: 99%